Particularities of the negative streamer propagation in homogeneous and inhomogeneous electric fields. Computer simulation - Manuilenko, O.V.; Golota, V.I. (Вопросы атомной науки и техники, 2013)
The results of numerical simulations of negative streamer propagation in nitrogen in the plane - to - plane and the needle - to - plane geometries are presented. Computer simulations has been performed by finite element method, which allows to accurately describe the boundaries of complicated shape. It is shown that the propagation velocity of the negative streamer in a nonuniform electric field (the needle - to - plane geometry) is always greater than its velocity in a uniform field (the plane - to - plane geometry) at the same electrical potentials on the electrodes. It is shown that with decreasing curvature radius of the needle the streamer propagation velocity increases. The growth of the streamer speed, with decreasing of the needle curvature radius, is stopped when the needle curvature radius reaches a certain critical size. It is shown that in the region of the strong nonlinearity, when the dynamics of the streamer propagation is determined by the space charge, its velocity as a function of the longitudinal coordinate is independent of the needle curvature radius. Приведены результаты численного моделирования методом конечных элементов распространения отрицательного стримера в азоте в геометриях плоскость–плоскость и игла–плоскость. Показано, что скорость распространения стримера в неоднородном поле (геометрия игла–плоскость) всегда больше его скорости в однородном поле (геометрия плоскость–плоскость) при одинаковых потенциалах на электродах. Показано, что при уменьшении радиуса кривизны иглы скорость распространения стримера возрастает. Рост продолжается до некоторого критического радиуса, после которого рост скорости стримера практически прекращается. Показано также, что в области сильной нелинейности, когда динамика распространения стримера определяется его объемным зарядом, его скорость, как функция продольной координаты, не зависит от радиуса кривизны иглы. Наведено результати числового моделювання методом кінцевих елементів поширення негативного стримера в азоті в геометріях площина–площина і голка–площина. Показано, що швидкість поширення стримера в неоднорідному полі (геометрія голка–площина) завжди більше його швидкості в однорідному полі (геометрія площина –площина) при однакових потенціалах на електродах. Показано, що при зменшенні радіуса кривизни голки швидкість розповсюдження стримера зростає. Зростання триває до деякого критичного радіуса, після якого зростання швидкості стримера практично припиняється. Показано також, що в області сильної нелінійності, коли динаміка розповсюдження стримера визначається його об'ємним зарядом, його швидкість, як функція поздовжньої координати, не залежить від радіуса кривизни голки.